Physiological Qualities Of Polyembryony Seeds And Zigotes Of Nangka (Artocarpus integra (Thumb) On Seed Production - Walingkas, Walingkas; Tumewu, Pemmy; Rantung, Meity Rosadelly (Sam Ratulangi University, 2023)
The aim of this research is to determine the polyembryonic properties of jackfruit seeds, whether the resulting polyembryonic seeds can be used as a contributor to seed production, to determine the number of seeds produced from embryonic characteristics and to determine the relationship between polyembryony and seedling growth. The research used a Randomized Block Design (RAK) with 5 treatments each: whole jackfruit zygotic seeds 1 (Z1), whole jackfruit polyembryony seeds 2 (PU2), whole jackfruit polyembryony seeds 3 (PU3), split jackfruit polyembryony seeds 2 (PB2) and polyembryonic seeds of split jackfruit 3 (PB3). Variables observed included: plant height, stem diameter and number of leaves. Data were analyzed using analysis of variance and the Least Significant Difference Test (LSD) 5%.The results of research on the germination of jackfruit seeds in the zygote seed treatment (Z1), 2 whole and 2 split polyembryonic seeds had a viability above 80%, so they could be used as a seed source. Keywords: Jackfruit, Polyembryony, Seed Production Abstrak Tujuan penelitian ini mengetahui sifat-sifat poliembrioni pada biji nangka apakah hasil biji poliembrioni yang dihasilkan dapat dijadikan sebagai penyumbang untuk produksi benih, mengetahui jumlah bibit yang dihasilkan dari sifat embrioni serta mengetahui hubungan antara poliembrioni dengan pertumbuhan bibit. Penelitian mengunakan rancangan Acak Kelompok (RAK) dengan 5 perlakuan masing-masing : benih Zigotik nangka utuh 1 (Z1), benih Poliembrioni nangka utuh 2 (PU2), benih poliembrioni nangka utuh 3 (PU3), benih poliembrioni nangka belah 2 (PB2) dan benih poliembrioni nangka belah 3 (PB3) Variabel yang diamati, meliputi: tinggi tanaman, diameter batang dan dan jumlah daun. Data dianalisis menggunakan analisis ragam dan Uji Beda Nyata Terkecil (BNT) 5 %. Hasil penelitian perkecambahan benih nangka pada perlakuan benih zigot (Z1), benih poliembrioni utuh 2 dan belah 2 mempunyai viabilitas diatas 80%, sehingga dapat dijadikan sebagai sumber benih. Kata Kunci : Nangka, Poliembrioni, Produksi Benih